Combined single-cell and spatial transcriptomics reveal the molecular, cellular and spatial bone marrow niche organization - Baccin, Chiara; Sabah, Jude al-; Trumpp, Andreas (Nature cell biology, 2020)
Baccin, Al-Sabah, Velten et al. use single-cell and spatially resolved transcriptomics to map the cellular, molecular and spatial organization of the endosteal, sinusoidal and arteriolar bone marrow niches.
Published 23 December 2019
Das PDF enthält zusätzlich einen Anhang von 19 Seiten
Gesehen am 13.01.2020